2002
DOI: 10.1108/10662240210415781
|View full text |Cite
|
Sign up to set email alerts
|

A conjoint analysis of voice over IP attributes

Abstract: The ability to transmit and process voice over Internet protocol (VoIP) networks has important implications for technology managers. Many companies today are rushing to bring different VoIP products to market with a wide variety of features. Managers will need to understand the tradeoffs associated with VoIP as compared to the Public Switched Telephone Network (PSTN). This paper measures the preference structures between IP telephony and PSTN services using conjoint analysis. The purpose is to suggest those Vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Many studies found that quality is still the priority for users. A study using conjoint analysis found that call quality is an important attribute when making a voice call (Zubey at al, 2002). Similarly, a study in 2008 focusing on Japanese customers was conducted using conjoint analysis.…”
Section: Overview Of the Voice Communication Market In Thailandmentioning
confidence: 99%
“…Many studies found that quality is still the priority for users. A study using conjoint analysis found that call quality is an important attribute when making a voice call (Zubey at al, 2002). Similarly, a study in 2008 focusing on Japanese customers was conducted using conjoint analysis.…”
Section: Overview Of the Voice Communication Market In Thailandmentioning
confidence: 99%
“…The price of long distance telecommunications is driving the move to cheaper alternatives (Zubey, Wagner, & Otto, 2002). VoIP is one of those options.…”
Section: Current Business Conditions Regarding Telephony and Datamentioning
confidence: 99%
“…Still, there are several disadvantages to using VoIP today, and some that users may find unacceptable. Quality of service (QoS), in some cases, does not meet voice grade quality transmission (Zubey, Wagner, & Otto, 2002).…”
Section: Current Business Conditions Regarding Telephony and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Martocchio, Webster and Baker (1993), Webster and Trevino (1995), Van de Wijngaert (1996, 1999, Bouwman & Van de Wijngaert (2002, 2003 and Zubey, Wagner & Otto (2002) use these research approaches in discussing media choice models, information needs in relation to media choice, e-commerce channel preferences, and Voice over IP. Furthermore, there are some studies in the area of next generation mobile services.…”
Section: Research Approachmentioning
confidence: 99%